Matrine disturbs the eimeria necatrix-induced loop of tuft cell-intestinal stem cell-goblet cell by inactivating IL-13/JAK2/STAT3 signaling - Geng-xiu Zan; Hao-zhan Qu; Jia Meng; Xiao-fan Wang; Hui-chao Yan; Xiu-qi Wang; Jia-yi Zhou (Poultry Science)
As sensors in the gut, tuft cells integrate a complex array of luminal signals to regulate the differentiation fate of intestinal stem cells (ISCs), which trigger a loop of tuft cell-ISC-goblet cell after parasitic infection. As a plant-derived alkaloid, Matrine plays a prominent role for standardizing ISC functions in Eimeria necatrix (EN)-exposed chicks. In this study, we investigated the modulation effects of Matrine on the specific intestinal epithelial cell loop in EN-exposed chicks in vivo and intestinal organoids (IOs) ex vivo. The results showed that EN infection resulted in swelling and hemorrhage of the jejunum, accompanied by the increase in levels of sIgA and inflammatory cytokines (IL-6, IL-1β, and TNF-α). And these inflammatory symptoms were effectively relieved by Matrine intervention. Concurrently, Matrine resisted the EN-induced increase in tuft cell numbers and levels of crucial pro-inflammatory factors (IL-25 and IL-13), while also reversing the differentiation of secretory cell progenitors into goblet cells. Importantly, Matrine impeded the upregulation of the inflammatory signaling pathway JAK2/STAT3 in EN-infected chicks and IOs. Conversely, exogenous supplementation of IL-13 or activation of STAT3 via Colivelin eliminated the standardization of the tuft cell-ISC-goblet cell loop by Matrine. Overall, our findings suggested that Matrine intercepted the tuft cell-ISC-goblet cell loop by reinstating IL-13/JAK2/STAT3 signaling after EN infection.